Characteristics of Tokiwadaira Neighbourhood Park in Matsudo, Japan: A space for the elderly - Pratiwi, Prita Indah; Furuya, Katsunori (Environment-Behaviour Proceedings Journal, 2018)
Tokiwadaira is one of the districts most populated by elderly in Japan. This study compared the preferences of danchi and apartment residents to examine the neighbourhood park preferences as well as neighbourhood park similarity. This research was conducted in three stages, including a spatial preference survey, analysis, and interpretation. A Welch’s t-test and correspondence analysis were applied. Results demonstrated three significant differences between danchi and apartment residents, namely park preference, length of visit, and preferred park elements. There were four similarities among Tokiwadaira neighbourhood parks. These results may help urban planners optimise existing features of neighbourhood parks to encourage use. Keywords: landscape preference; neighbourhood parks; resident participation eISSN: 2398-4287 © 2018. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. https://doi.org/10.21834/e-bpj.v3i9.1513